Adopting Elementary School Educational Systems in Taiwan to Improve Indonesian Education - Efendi, Moch. Yusuf; Lien, Hsi-Nancy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This paper intends to review and adopting from the Elementary school educationalsystems in Taiwan. The aim give knowledge to the citizens of the nation who are active in the world of education in the following three ways: how is the portrait of the Taiwan elementary school educational system, how the Taiwan education system compares with the Indonesian educational system and what lessons can be taken from the practice of implementing the educational system in Taiwan. The important things reviewed in the context of the elementary school educational systems in Taiwan are the cornerstone of the philosophy of education, politics and the purpose of education, the structure and type of education, types of schools, and management of education in Taiwan. Then the points are compared with the elementary school educational system in Indonesia. The method used for this paper are descriptive qualitative and literature studies. This study describes, examines, analyzes and interprets the current conditions. While the literature method is amethod of collecting data that is done by adopting the necessary data from the related literature. Some of the important points related to the elementary school educational systems in Taiwan need to be our concern and to adopt it to improve the quality of education in Indonesia.